Vaccination in Older Adults: An Underutilized Opportunity to Promote Healthy Aging in India - Vora, Agam (Drugs Aging, 2021)
Over the last 50 years, the Indian population aged 50 years and above (older adults) has quadrupled and is expected to comprise 404 million people in 2036, representing 27% of the country’s projected population. Consequently, the contribution of chronic disease to older adults’ total burden of diseases in India is likely to escalate. Disease burden is notably amplified by immunosenescence, a deterioration of the immune system that develops with age, leading to increasing susceptibility to infectious diseases and other comorbidities. Older adults with infectious diseases have a higher incidence and likelihood of life-threatening comorbidities such as coronary artery disease, arrhythmia, stroke, myocardial infarction, hypertension, dyslipidemia, and diabetes mellitus. Therefore, immunization of older adults through vaccination might greatly reduce the burden imposed by vaccine preventable infectious diseases in this population. Here, we review evidence relevant to the disease burden among adults aged ≥ 50 years in India, and existing vaccination recommendations. Furthermore, we suggest a set of routine vaccinations for healthy older adults in India. There is a clear mandate to recognize the contributions of older adults to society and embrace strategies promoting healthy aging, which is described by the World Health Organization as the process of developing and maintaining functional ability and well-being in older age. Increasing vaccination awareness and coverage among older adults is an important step in that direction for India.